2023
DOI: 10.57187/smw.2023.40029
|View full text |Cite
|
Sign up to set email alerts
|

Procedures of brain death diagnosis and organ explantation in a tertiary medical centre – a retrospective eight-year cohort study

Abstract: AIMS OF THE STUDY: To assess the frequency and variables associated with the need for ancillary tests to confirm suspected brain death in adult patients, and to assess the time from brain death to organ explantation in donors. We further sought to identify modifiable factors influencing the time between brain death and start of surgery. METHODS: Medical records and the Swiss organ allocation system registry were screened for all consecutive adult patients diagnosed with brain death at an intensive care u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In 2020, 21.3% of organ donors underwent confirmatory testing in Denmark, which is in line with previous studies from other countries (24–26%) ( Sayan, 2020 ; Grzonka et al, 2023 ). These studies also reveal an increased use of ancillary tests, further emphasizing the scope and importance of appropriate protocols for ancillary tests in the determination of BD/DNC.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…In 2020, 21.3% of organ donors underwent confirmatory testing in Denmark, which is in line with previous studies from other countries (24–26%) ( Sayan, 2020 ; Grzonka et al, 2023 ). These studies also reveal an increased use of ancillary tests, further emphasizing the scope and importance of appropriate protocols for ancillary tests in the determination of BD/DNC.…”
Section: Introductionsupporting
confidence: 89%
“…This corroborates the notion that time has a negative effect on donor status, highlighting the need to carefully chose and interpret ancillary investigations during BD/DNC determination. In a previous study, the duration of the BD/DNC protocol was associated with negative effects on donations, as increasing time intervals created the potential for confusion about the diagnosis and lead to withdrawal of consent by patient families ( Grzonka et al, 2023 ). In another study, no correlation was seen between the consent to organ donation and the time from ICU admission until the completion of the BD/DNC protocol ( Sayan, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] In a study conducted in Switzerland, 50% of the 76 cases who accepted to be donors between 2013 and 2020 were male and 50% female, and the median age of the cases was 57. [ 12 ] In a study conducted with 116 cases in the Arabian peninsula between 2011 and 2012, it was found that 82.75% male/17.25% female, with a mean age of approximately 44. [ 13 ] They divided the cases diagnosed as brain death in South Korea between 2000–2010 and 2011–2020 into two groups.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 , 10 , 15 ] Ancillary tests were used at a rate of 24% in Sweden and 95% in Spain. CT angio and EEG were used most frequently, [ 12 , 16 ] respectively. The use of brain death protocol and ancillary test differs in Asian and Pacific countries, except for 5 countries.…”
Section: Discussionmentioning
confidence: 99%
“…42 Further, in a 2023 retrospective study on use of ancillary testing at a Swiss tertiary medical center from 2013 to 2020, Grzonka et al reported that 18/78 (24%) patients had ancillary testing, and use of ancillary testing was more common after HIBI compared with other etiologies of BD/DNC (61% vs. 24%, p = 0.008). 121 Additionally, in a systematic review and meta-analysis of papers on the diagnostic accuracy of ancillary testing through 2022, Neves Briard et al identified 137 relevant publications and reported similar pooled sensitivities (range of 0.82–0.93) with greater heterogeneity within (σ = 0.10–0.15) than between (σ = 0.04) ancillary test types in patients who met clinical criteria for BD/DNC. 122 They noted unclear or high risk of bias, and emphasized the need for high-quality studies to evaluate ancillary tests.…”
Section: Review Of the Wbdp And Updates Since Publicationmentioning
confidence: 99%